“GRIEF AND RESILIENCE LIVE TOGETHER”: AN ASSESSMENT OF ARTHUR MILLER’S DEATH OF A SALESMAN - Philomena Ama Okyeso Yeboah; Paul Otoo; James Gyimah Manu; Philip Kwame Freitas (University of Muhammadiyah Malang, 2022)
The present study was carried out to assess Mrs. Obama’s assertion, “grief and resilience live together”, in Miller’s tragedy, Death of a Salesman, from the theoretical perspectives of Marxism and Psychoanalysis. Using a qualitative content analysis, the paper finds that even though the protagonist meets his tragic end through his sufferings and disillusion, he displays unparalleled courage, resilience and optimism, as a common man, in a battle with the capitalist society. The paper affirms the afore-said statement and limns the defects of capitalism and its consequences on its victims – more so their psyche and mental state. With this paper, the researchers seek to expose the ills of capitalism and its devastating effects on the working-class members of the society.